Effect of Consecutive Firings on the Optical and Mechanical Properties of Silicate and Lithium Disilicate Based Glass-Ceramics - Campanelli de Morais, Dayana; de Oliveira Abu-izze, Fernanda [UNESP]; Rivoli Rossi, Natália [UNESP]; Gallo Oliani, Marcelo [UNESP]; de Assunção e Souza, Rodrigo Othávio; de Siqueira Anzolini Saavedra, Guilherme [UNESP]; Bottino, Marco Antonio [UNESP]; Marques de Melo Marinho, Renata [UNESP] (Wiley, 2021)
Purpose: To evaluate the effect of multiple firings on the optical and mechanical properties of two dental CAD/CAM glass-ceramics. Materials and Methods: A total of 45 specimens of each lithium disilicate-LD (IPS E.max CAD, Ivoclar Vivadent) and zirconia lithium silicate-ZLS (Vita Suprinity, Vita Zahnfabrik) material were prepared in a disk shape. These specimens were divided into three groups according to two factors: “type of ceramic” (LD and ZLS) and “numbers of firings” (Control 2F-two firings, 5F-five firings and 7F-seven firings). The firing cycles were performed according to the manufacturer's recommendations. X-ray diffraction was additionally performed to determine crystalline phases in each group, spectrophotometry was used to determine color and translucency variation, and biaxial flexural strength (BFS) evaluated the mechanical behavior. The data were analyzed individually using two-way ANOVA tests and Tukey's test at α = 0.05. Results: The crystalline phases did not present any change after multiple firings for either of the analyzed materials. Both commercial materials showed a significant difference regarding translucency at 7F (p = <0.01), and ZLS presented a difference in color higher than one (ΔE > 1) at 5F and 7F. Regardless of the number of firings, LD presented a higher BFS compared to ZLS (p = <0.001), and a significant increase in BFS comparing 2F and 7F (p = <0.024). Conclusion: The use of multiple firings can significantly alter the color, translucency, and mechanical strength of CAD/CAM ceramics.
Keywords: Color change; flexural strength; fractography; glass-ceramics; repeated firings; X-ray diffraction